Three-dimensional analysis of the precipitation behavior of 18Cr–9Ni–3Cu–Nb–N steel at 973 K. (15th July 2021) - Hatakeyama, Tomotaka; Sawada, Kota; Hara, Toru; Sekido, Kaoru; Kimura, Kazuhiro
Abstract: Microstructure development of 18Cr–9Ni–3Cu–Nb–N steel during creep was discussed by observing the grip portion of the crept specimen that ruptured after 50214.3 h at 973 K. Focused ion beam-scanning electron microscopy (FIB-SEM) serial sectioning and image processing with machine learning were combined for the three-dimensional visualization of the precipitation behavior of the steel. It was revealed that coarsening of σ phase induce the depletion of M23 C6 phase on the grain boundary and aggregation of Cu phase at the interface between the σ phase and the matrix. These microstructural changes related to the σ phase formation were suggested to cause premature failure in the longer-term creep due to the reduced contribution of grain boundary precipitation strengthening by M23 C6 phase and precipitation strengthening by Cu phase around the σ phase. Graphical abstract: Image, graphical abstract